The hidden hedgehog of the pituitary: hedgehog signaling in development, adulthood and disease of the hypothalamic-pituitary axis - Bian, Yehan; Hahn, Heidi; Uhmann, Anja (Frontiers in Endocrinology, 2023)
Hedgehog signaling plays pivotal roles in embryonic development, adult homeostasis and tumorigenesis. However, its engagement in the pituitary gland has been long underestimated although Hedgehog signaling and pituitary embryogenic development are closely linked. Thus, deregulation of this signaling pathway during pituitary development results in malformation of the gland. Research of the last years further implicates a regulatory role of Hedgehog signaling in the function of the adult pituitary, because its activity is also interlinked with homeostasis, hormone production, and most likely also formation of neoplasms of the gland. The fact that this pathway can be efficiently targeted by validated therapeutic strategies makes it a promising candidate for treating pituitary diseases. We here summarize the current knowledge about the importance of Hedgehog signaling during pituitary development and review recent data that highlight the impact of Hedgehog signaling in the healthy and the diseased adult pituitary gland.